Proposing a model on customer acceptance of Bank Rakyat’s Ar-Rahnu scheme with its determinants / Rupidah Abdul Razak - Abdul Razak, Rupidah (2011)
According to the topic chosen, “Proposing a Model on Customer Acceptance of Bank Rakyat’s Ar-Rahnu Scheme with Its Determinants”, the model is created to find the factors that influence customer acceptance on Ar-Rahnu Scheme and to find the result for the finding. The objective of this study is to determine the factors that influence the customer acceptance on Ar-Rahnu Scheme provided by Bank Rakyat in Indera Mahkota. Considering this objective, the study tends to develop a model or theoretical framework to explain the factors influence consumers’ acceptance of Ar-Rahnu Scheme in Bank Rakyat. The model was tested with a survey sample which is 100 of respondents in Bank Rakyat Bandar Indera Mahkota. The model was labeled as SPIDCA model which stands for all independent variables (Shariah view, pledge asset, income, distance between house and pawnshop, customer service and advertisement. This model also treated as an eye-opener about the importance of having that system in Indera Mahkota, Kuantan. A set of questionnaires was distributed to the respective respondents. Several factors that being discussed in this research are demographic factors and elements that contributes to the customer acceptance. The data is analyzed using descriptive analysis, frequency, reliability testing and Regression Analysis of Statistical Package for Social Sciences (SPSS)